No evidence for the in vivo induction of genomic instability by low doses of 137Cs gamma rays in bone marrow cells of BALB/cJ and C57BL/6J MICE - Rithidech K. (2017)
In spite of extensive research, assessment of potential health risks associated with exposure to low-dose (≤ 0.1 Gy) radiation is still challenging. We evaluated the in vivo induction of genomic instability, expressed as late-occurring chromosome aberrations, in bonemarrow cells of two strains of mouse with different genetic background, i.e. the radiosensitive BALB/cJ and the radioresistant C57BL/6J strains following a whole-body exposure to varying doses of 137Cs gamma rays (0, 0.05, 0.1, and 1.0 Gy). A total of five mice per dose per strain were sacrificed at various times post-irradiation up to 6 months for sample collections. Three-color fluorescence in situ hybridization for mouse chromosomes 1, 2, and 3 was used for the analysis of stable-aberrations in metaphase-cells. All other visible gross structural-abnormalities involving non-painted-chromosomes were also evaluated on the same metaphase-cells used for scoring the stable-aberrations of painted-chromosomes. Our new data demonstrated in bone-marrow cells from both strains that low doses of low LET-radiation (as low as 0.05 Gy) are incapable of inducing genomic instability but are capable of reducing specific aberration-types below the spontaneous rate with time postirradiation. However, the results showed the induction of genomic instability by 1.0 Gy of 137 Cs gamma rays in the radiosensitive strain only. © 2012 University of Massachusetts.